2021
DOI: 10.21203/rs.3.rs-461056/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Pilot Study of a Culturally-Appropriate, Educational Intervention to Increase Participation in Cancer Clinical Trials Among African Americans and Latinos

Abstract: Aim: Culturally-appropriate, educational programs are recommended to improve cancer clinical trial participation among African Americans and Latinos. This study investigated the effect of a culturally-appropriate, educational program on knowledge, trust in medical researchers, and intent for clinical trial participation among African Americans and Latinos in Middle Tennessee.Method: Trained community health educators delivered a 30-minute presentation with video testimonials to 198 participants in 13 town hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…While this increase was statistically significant, it is worth noting that this was a small practical change (approximately 1 additional item answered correctly). This finding parallels several pre-post designed studies of cancer clinical trial educational interventions that have also reported minor improvements for total knowledge [13,14] and individual questions [15] among ethnic minority community respondents. Moreover, the prior samples of Black and Latino respondents demonstrated identical knowledge improvements across ethnicity [13,14], as in the current study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…While this increase was statistically significant, it is worth noting that this was a small practical change (approximately 1 additional item answered correctly). This finding parallels several pre-post designed studies of cancer clinical trial educational interventions that have also reported minor improvements for total knowledge [13,14] and individual questions [15] among ethnic minority community respondents. Moreover, the prior samples of Black and Latino respondents demonstrated identical knowledge improvements across ethnicity [13,14], as in the current study.…”
Section: Discussionsupporting
confidence: 85%
“…This finding parallels several pre-post designed studies of cancer clinical trial educational interventions that have also reported minor improvements for total knowledge [13,14] and individual questions [15] among ethnic minority community respondents. Moreover, the prior samples of Black and Latino respondents demonstrated identical knowledge improvements across ethnicity [13,14], as in the current study. It is notable that the one other randomized controlled trial of a cancer clinical trials education program did not yield any improvement in knowledge [16].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…40 Successful efforts to increase Hispanic/Latinx accrual to clinical trials include culturally appropriate outreach and education, improving the informed consent process, use of patient navigators, and building community partnerships. [41][42][43][44] In addition, the representation of diverse voices among patient advocates is imperative to the design of patient-centered and culturally appropriate studies.…”
mentioning
confidence: 99%